Design of process parameters for the manufacturing of wrapped connections with single solid round wires using the explicit finite element analysis - Hefner, Florian; Praß, Julian; Kirchner, Philipp; Franke, Jörg (Procedia CIRP, 2020)
Keywords: process simulation; wrapped connections; explicit finite element analysis

Integrated approach enabling robust and tolerance design in product concept development - Götz, Stefan; Kirchner, Philipp; Schleich, Benjamin; Wartzack, Sandro (Design Science, 2021)
Along with the ever-increasing customer demands, early consideration of variation in terms of robust design is important to avoid expensive iterations in the product development. However, existing methods are detached from the development process and can therefore only be applied at a late stage or only with comprehensive expert knowledge. Especially in the concept stage, where the geometry of a product is not yet defined and the optimisation potential is high, effective solution proposals for systematic consideration of variation are lacking. Therefore, this paper describes a new integrated approach facilitating robust and tolerance design in the concept stage. The novelty of the approach using ontologies and graph-based visualisation is the close linkage of product development and tolerance knowledge, which allows automation and helps to avoid time- and cost-intensive iteration loops. As a result, a robust and tolerance-compliant concept design, an initial qualitative tolerance specification and instructions for the further tolerancing process are already available at the end of the concept stage. The applicability and the benefits of the approach are illustrated by representative case studies and a user study allowing a critical comparison between the conventional, mostly subjective procedure and the presented approach.
Keywords: robust; designtolerance; designconcept; designgraphontology

Robustheitsbewertung von Produktkonzepten auf Basis von Graphen - Kirchner, Philipp; Götz, Stefan (Summer School Toleranzmanagement - Beiträge zur 4. Summer School - September 2020, 2020)